Effectivity of 5% Dextrose-Diluted and Ringer Lactate-Diluted Propofol to Reduce Intravenous Injection Pain in Pediatric Patient - Dian Raseka Parna; Arie Utariani; Elizeus Hanindito (Indonesian Journal of Anesthesiology and Reanimation, 2020)
Introduction: Propofol has been known as one out of many inductive drugs which, can cause pain during intravenous injection. There has been a high prevalence of injection pain in pediatric patients. The mechanism of injection pain has not been known. Some therapeutic methods have been tested to reduce the pain, with several success rates. Objective: To compare the effectivity of 5% dextrose-diluted propofol and ringer lactate-diluted propofol, with dilution comparison of 1:1, in their role to reduce intravenous injection pain in pediatric patients, from age 2-15 years old during elective surgery in the Integrated Surgical Building Center of Dr. Soetomo General Hospital Surabaya. Method and Material: Forty-five patients PS ASA I-II, which fulfill inclusion criteria, were induced with general anesthesia. Patients had been selected randomly into three groups. Group I (control group) were injected with propofol without dilution. Group II was injected with propofol with a dilution of 5% dextrose, into 5 mg/ml liquid. Group III was injected with propofol with a dilution of ringer lactate, into 5 mg/ml liquid. Result and Discussion: The level of pain was evaluated afterward, with responding to the four-point scale and spontaneous expression. Patients' blood pressure, mean arterial pressure, heart rate, and oxygen saturation were also examined after injection. Compared to the control group, those in groups with 5% dextrose-diluted and ringer lactate-diluted propofol are not effective in reducing intravenous injection pain, with analytical statistics p=0.503 (p > 0.05). Also, the dilution of propofol has no significant difference to the hemodynamic measurement of patients. Systolic and diastolic blood pressure, and mean arterial pressure were declined after the induction, but statistically insignificant. The heart rate of patients was inclined but also not significant. Conclusion: 5% dextrose-diluted and ringer lactate-diluted propofol with a comparison of 1:1 were not significantly effective in reducing intravenous injection pain in pediatric patients.